Analysis of Physics Learning Outcomes Based on High School Students' Learning Styles: A Meta-Analysis Study - Safira, Sitta; Jannah, Misbahul; Arsad, Nurazidawati Mohamad (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
Learning physics in senior high school is often a challenge because the material requires theoretical and mathematical understanding, especially if the learning method does not pay attention to the learning style of students. This study aims to analyze articles related to physics learning outcomes based on the learning styles of high school students using a meta-analysis approach. This research is a meta-analysis of previous research published in the 2015-2024 timeframe. This research provides guidance for teachers in designing effective learning strategies according to the needs of students. The results showed that visual learning style is the most dominant in supporting physics concept understanding, followed by auditory style, and finally kinesthetic style. However, other factors such as motivation and teaching methods also affect learning outcomes. The conclusion of this study states that learning style is not the only factor that affects physics learning outcomes. A multimodel learning approach is important to improve learning outcomes effectively and inclusively.